From Entomological Disaster to Agricultural Modernization, the Effect of Pink Bollworm on Cotton Farming in Çukurova (1914-1928) - Okan Ceylan (Belleten)

(untitled)
Since the second half of the 19th century, pink bollworm, which has been effective on a global scale, spread to Çukurova as a result of cotton seed imports from Egypt after the First World War (the WWI). In 1924 and 1925, pink bollworm, which had a negative impact on cotton yields, was initially seen as an entomological problem in cotton, but turned into a social, economic and political problem due to the key importance of cotton in Türkiye’s foreign trade, textile industry and rural development. As a matter of fact, the agricultural control against pink bollworm led to technical advances, scientific innovations and legal regulations in cotton cultivation. In this context, Adana Seed Breeding Station was established in 1925 and Mersin Agricultural Control Laboratory in 1926. In the literature, the cotton history of Çukurova is mostly discussed in terms of society, state and geography. This study, on the other hand, goes one step beyond the anthropocentric perspective and explains the historical process through the relationship of partnership and interdependence between cotton, society and the state. Spatially, the role of pink bollworm in the socio-economic, scientific and technical transformation of Çukurova cotton farming is explored, taking into account the global dimension. Periodically, this study focuses on the transition phase from the Ottoman Empire to the Republic and examines the period from the WW I, when the pest began to appear, to the Great Depression of 1929, when planned industrial development models or Keynesian economic policies that envisioned state interventionism began to be implemented.